2002
DOI: 10.1515/bc.2002.212
|View full text |Cite
|
Sign up to set email alerts
|

cis-4-Methylsphingosine Phosphate Induces Apoptosis in Neuroblastoma Cells by Opposite Effects on p38 and ERK Mitogen-Activated Protein Kinases

Abstract: Intracellular phosphorylation of cis-4-methylsphingosine was previously shown to result in a metabolically stable compound that accumulates in Swiss 3T3 fibroblasts and mimics the mitogenic effect induced by the short-lived sphingosine metabolite, sphingosine-1-phosphate. In the present study incubation of neuroblastoma B104 cells with cis-4-methylsphingosine (10 microM) also resulted in an intracellular accumulation of its phosphorylated derivative that was, however, associated with the concentration-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 37 publications
5
21
1
Order By: Relevance
“…3B) and cell death (Fig. 1B) is also consistent with reports showing that a downregulation in ERK1/2 activation accompanies p38 MAPK-mediated apoptosis in both neuronal and nonneuronal cells [17,20,24].…”
Section: Discussionsupporting
confidence: 91%
“…3B) and cell death (Fig. 1B) is also consistent with reports showing that a downregulation in ERK1/2 activation accompanies p38 MAPK-mediated apoptosis in both neuronal and nonneuronal cells [17,20,24].…”
Section: Discussionsupporting
confidence: 91%
“…Because our data clearly show that safingol is only converted into less-bioactive compounds like dihydroceramide and more complex sphingolipids, its antineoplastic activity most probably cannot be explained by the formation of l-threo-ceramide, as suggested before (37). From our results, it appears more likely that the cytotoxic effect of safingol is a result of blocking sphingosine kinase on the one hand (12,39,40) and PKC on the other hand (9,38). However, we cannot exclude that the different cell systems used in different studies might explain the different results.…”
Section: Discussionsupporting
confidence: 48%
“…We have recently shown that in neuroblastoma cells (12) as well as in primary cultured neurons (unpublished observations), the inhibitory effect of safingol (20 M) on sphingosine kinase catalyzed phosphorylation of the synthetic sphingosine analog cis-4-methylsphingosine decreases over time. These findings indicate that, although safingol is a nonnatural stereoisomer, it appears to be efficiently metabolized by neuronal cells.…”
mentioning
confidence: 93%
“…Genomic DNA Analysis-Genomic DNA analysis was performed as described previously (17). In brief, cells were detached with a cell lifter in the respective medium and centrifuged (2000 ϫ g, 10 min, 4°C), thus collecting both adherent and detached cells.…”
Section: Methodsmentioning
confidence: 99%